Regional differences in patient age and prostate cancer characteristics and rates of treatment modalities in favorable and unfavorable intermediate risk prostate cancer across United States SEER registries - Wenzel, Mike; Collà Ruvolo, Claudia; Nocera, Luigi; Würnschimmel, Christoph; Tian, Zhe; Shariat, Shahrokh F; Saad, Fred; Briganti, Alberto; Graefen, Markus; Becker, Andreas; Mandel, Philipp; Chun, Felix K H; et al. (Cancer epidemiology, 2021)
BACKGROUND: Intermediate risk (IR) prostate cancer (PCa) is a highly heterogeneous entity and can be distinguished into favorable and unfavorable IR PCa according to biopsy, PSA and cT-stage characteristics. These differences may translate into differences in treatment type. METHODS: We tested for differences in PCa tumor characteristics and differences in active treatment rates (radical prostatectomy [RP], external beam radiotherapy [EBRT]) according to Surveillance, Epidemiology and End Results (SEER) registry (2010-2015) in favorable and unfavorable IR PCa. Data were stratified according to individual SEER registries. Further analyses additionally adjusted for PCa baseline characteristics (PSA, cT stage, biopsy Gleason group grading [GGG], percentage of positive biopsy cores). RESULTS: Tabulations according to SEER registries showed that, in favorable IR vs. unfavorable IR, the rates of RP and EBRT respectively ranged from 30.0 to 54.3% vs. 30.3-55.5 % and 8.3-44.7 % vs. 11.5-45.5 %. Differences in age and baseline PCa tumor characteristics also existed in both favorable and unfavorable IR across SEER registries. After adjustment for those baseline patient and PCa characteristics (PSA, cT stage, GGG, percentage of positive biopsy cores), RP and EBRT rates exhibited virtually no residual differences across individual SEER registries, in both favorable (36.0-41.0 % and 26.8-28.1 %) and unfavorable IR PCa (39.2-42.0% and 31.1-33.5 %). CONCLUSION: Important differences may be identified in treatment rates within the examined 18 SEER registries in favorable and in unfavorable IR PCa. However, the observed differences are virtually entirely explained by differences in baseline PCa characteristics.
Keywords: prostatický specifický antigen; Treatment variability; Unfavorable; Favorable; Registries; lidé; Neoplasm Grading; nádory prostaty; Prostatectomy; Prostatic Neoplasms; Intermediate risk; Prostate-Specific Antigen; stupeň nádoru; Spojené státy americké; Male; United States; prostatektomie; registrace; mužské pohlaví; Humans